Analysis of Lactobacillus rhamnosus GG in Mulberry Galacto-Oligosaccharide Medium by Comparative Transcriptomics and Metabolomics - Li, Erna; Zhu, Qiaoling; Pang, Daorui; Liu, Fan; Liao, Sentai; Zou, Yuxiao (Frontiers in Nutrition, 2022)
Lactobacillus rhamnosus GG (LGG) has strong acid resistance and can survive passing through the stomach to colonize the intestines, where it promotes the growth of beneficial bacteria. Prebiotics such as mulberry galacto-oligosaccharide (MGO), mulberry polysaccharide solution (MPS), and galactooligosaccharides (GOS) promote LGG proliferation, and MGO has the greatest effect. After culturing LGG with prebiotics, changes in gene expression were studied at the transcriptomic and metabolomic levels. The results showed that, in the stable 24-hour growth period of cultivation, approximately 63% and 132% more differential genes were found after MPS and MGO were added to the MRS medium, respectively, than after GOS was added, and the numbers of up-regulated genes were about 18% and 66% higher with MPS and MGO, respectively, than GOS. Analysis using the KEGG database revealed that, when LGG was cultured with MGO, 120 genes that were up-regulated as the growth rate increased were mainly enriched in pathways such as membrane transport, amino acid metabolism, and carbohydrate metabolism. The genes gatB and gatC were up-regulated for galactose metabolism, and bglA was up-regulated in the glycolysis/gluconeogenesis pathway. The qRT-RCR results, which were in agreement with the RNA-seq, indicated the genes involved in the proliferation effect of LGG were up-regulated. UDP-glucose may be a key metabolite for MGO to promote LGG proliferation.